2009
DOI: 10.1177/1094428109335571
|View full text |Cite
|
Sign up to set email alerts
|

Interviewing Reluctant Respondents: Strikes, Henchmen, and Gaelic Games

Abstract: This paper deals with interviewing reluctant respondents. The analysis is used to construct

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
59
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 58 publications
(63 citation statements)
references
References 32 publications
1
59
0
3
Order By: Relevance
“…As similarly reported by Dundon and Ryan (2010), engagement with politically astute activists was essential to cement researcherparticipant empathy, to move beyond description and into a space where interviewees could feel free to discuss contentious issues. This was especially important given that members felt previous research was less than transparent with the CVP as a collective entity.…”
Section: Trust and Empathy-building In Participatory Action Researchmentioning
confidence: 99%
“…As similarly reported by Dundon and Ryan (2010), engagement with politically astute activists was essential to cement researcherparticipant empathy, to move beyond description and into a space where interviewees could feel free to discuss contentious issues. This was especially important given that members felt previous research was less than transparent with the CVP as a collective entity.…”
Section: Trust and Empathy-building In Participatory Action Researchmentioning
confidence: 99%
“…Furthermore, some of the deeper and richer sociological studies on workplace relations have a tendency to identify emergent themes postresearch (Dundon and Ryan, 2010). Further scrutiny of the aims of our various research projects showed that the data offered considerable scope for integrating the evidence along several unifying and emergent themes that are important to contemporary labour process analysis.…”
Section: Methodsmentioning
confidence: 99%
“…We therefore established criteria for an ex-post research design which allowed us to assess changes over time in a more holistic way than shorter or snapshot case reports, utilizing a staged approach to the re-analysis of data (see also Dundon and Ryan, 2010). The first stage involved reviewing the case organizations following Peetz's (2002) model to establish a range of managerial de-collectivizing strategies.…”
Section: Methodsmentioning
confidence: 99%
“…For instance, Dundon and Ryan (2010) look at 1 2 3 4 5 6 7 8 9 10 11 12 13 14 15 16 17 18 19 20 21 22 23 24 25 26 27 28 29 30 31 32 33 34 35 36 37 38 39 40 41 42 43 44 45 46 47 48 49 50 51 52 53 54 55 56 57 58 59 60 J o u r n a l o f O r g a n i z a t i o n a l E t h n o g r a p h y 3 establishing rapport, Tapani (2009) investigates the roles a researcher might fulfil, Pezalla, Pettigrew and Miller-Day (2012) query the level of disclosure a researcher should provide, Conquergood provides a model for avoiding 'ethical pitfalls' (1985, p.4), and Cunliffe and Karunanayake (2013, p.371) model a series of 'multiple identities' for consideration. However, the dynamics of achieving this 'secondary access', which we refer to as 'gaining acceptance', and which is crucial to the quality of any data capture tend to be implicitly rather than explicitly covered.…”
Section: Gaining Acceptancementioning
confidence: 99%